Technoeconomical analysis of a residential photovoltaic vapour compression air conditioning system - Choo, Shinn Chei (2005)
Photovoltaic (PV) is becoming a significant solar applications. Air conditioning is one of the basic needs for residential indoor comfort in tropical areas. A vapour compression air conditioning (VCAC) unit powered by PV is evaluated in this thesis by simulations. For energy-saving purpose, the VCAC unit is working with R134a, and variable compressor speed and condenser air mass flow rate are assumed. A typical residential house located in Senai is modeled and simplified cooling load temperature differential (CLTD) is used to find the peak load and determine the cooling capacities. Based on the peak load demands, psychrometric study is performed and VCAC model is developed to calculate the power supply needed. Then a crude stand-alone PV (SAPV) system size is predicted. To estimate the SAPV VCAC system performance, long-term average and detailed approaches are employed. The former adapted the simplified design method proposed by Hove (2000). It is found that without backup utility, 42.336 m2 of PV array area and 441.14 Ah of battery capacity are required to achieve annual solar fraction of 0.9, using PV mean efficiency of 0.13. In the latter approach, transfer function method (TFM) and VCAC simulations are performed to compute the hourly cooling loads. A detailed modeling of SAPV system based on generality usage is developed and system performance for seven days during the highest cooling demands is studied. The simulations results are discussed and parametric analysis are shown. The SAPV VCAC system is found to be not cost-effective due to efficiency constraint of PV technology and high PV capital costs. Electricity cost of minimum RM1/kW will make PV applications favourable. The simulation methodology requires empirical data to verify. Recommendations are made for improved computations. However, this study believes PV still has potential beneficial effects for large-scale residential energy applications.